The effect of segment joints on the thermo-hydro-mechanical response of energy tunnels - Hu Fan; Mei Yin; Guozhu Zhang; Yi Rui; Zhengheng Gan (Computers and Geotechnics, 2026)

Molecular-level source contribution of dissolved organic matter in a typical plateau lake using end-member mixing analysis based on spectroscopic, stable isotope and molecular fingerprint - Yunxuan Cheng; Shasha Liu; Rui Fu; Yi Ren; Yuxuan Zhang; Ziwen Yin; Fengchang Wu (Journal of Hydrology, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

A novel multiple imputation approach with recursive feature elimination BiLSTM for spatiotemporally seamless Landsat NDVI reconstruction - Guodong Zhang; Gaofei Yin; Yimin Ni; Yi Zhang; Rui Chen; Meilian Wang; Aleixandre Verger (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Earthworms counteract drought-induced impairment of wheat performance at the jointing stage regardless of microplastic type - Ruixin Du; Hanwen Cui; Ying Liu; Rui Wu; Yi Zhang; Chuanxiong Huang; Conghui Liu; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

A novel dual-mode sensor based on green-synthesized AuNPs and natural nitrogen-doped CQDs for tobramycin detection: enhanced sensitivity and specificity - Qiang Li; Rui-ling Yin; Xing-yi Yang; Yi-xin Xu; Yan-bing Leng; Xin Liu (Food Research International, 2026)

Tracking the fate of organophosphate esters: from occurrence to risk in the lower Yangtze River water - Yi Zhou; Wenxuan Ma; Wanyu Li; Ge Yin; Jiajun Chang; Yao Xiao; Zhiliang Zhu; Rui Wang; Yanling Qiu (Environmental Science and Pollution Research, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Nanozyme-catalytic colorimetric microfluidic paper-based analytical device for rapid detection of miRNA-21 - Ke Shi; Rui Yi; Mengxi Yin; Xiaoli Wang; Yuting Zhang; Nandi Zhou (Systems Microbiology and Biomanufacturing, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Reclassification of Sphingobium baderi Kaur et al. 2013 as a Later Heterotypic Synonym of Sphingobium wenxiniae Wang et al. 2011 - Syed Raziuddin Quadri; Kattia Nuñez-Montero; Patricio Arce-Johnson; Manda Sathish; Ngoc Tung Quach; Yi-Rui Yin; Manik Prabhu Narsing Rao (Current Microbiology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Typology-driven framework for revitalizing urban leftover spaces: Systematic review of practices and future research directions - Rui Qiao; Yi Sun; Siqiang Wang; Bo Lan; Chun Yin Chung (Land Use Policy, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

A comprehensive review of m6 A methylation in coronary heart disease - Mei-Ning Diao; Yi-Jv Lv; Hui Xin; Yin-Feng Zhang; Rui Zhang (Journal of Molecular Medicine, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Discovery of the earliest Devonian conodonts from Xinjiang, Northwest China - Jia-Yi Yin; Ladislav Slavík; Jian-Feng Lu; Juan Ma; Yi-Long Liu; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Comparison of the Intestinal Microbiota Composition and Function of Red Claw Crayfish (Cherax quadricarinatus) Cultured in Ponds and Rice Fields - Libin Huang; Tianhe Lu; Xiaohua Lu; Jingu Shi; Yin Huang; Xuesong Du; Dapeng Wang; Yi Liang; Yanju Lei; Lianggang Wang; Rui Wang; Huizan Yang (Fishes, 2024)
The growth environment significantly influences the intestinal microbiota of aquatic organisms. We investigated the composition and functional differences in the intestinal microbiota of red claw crayfish (Cherax quadricarinatus) in rice fields (RB) and ponds (PB) by 16S rDNA high-throughput sequencing technology. The results indicate that the Shannon, Simpson, Sobs, Chao1, and ACE indices of PB are all higher than those of RB, demonstrating greater diversity and richness of intestinal microbiota. The dominant phyla in the intestinal microbiota of the Cherax quadricarinatus were Proteobacteria, Tenericutes, and Firmicutes. Tenericutes and Proteobacteria were significantly more abundant in the RB than in the PB, while Planctomycetes and Firmicutes were significantly more abundant in the PB than in the RB. The results of network correlation analysis indicate that Proteobacteria and Firmicutes exhibit strong connectivity with other microbial groups in the gut microbiota of Cherax quadricarinatus, showing significant centrality. They play an important role in the interactions within the gut microbiota community. The dominant bacterial genera in the Cherax quadricarinatus’s gut were Citrobacter, Candidatus_Bacilloplasma, and Clostridium_sensu_stricto_1. The abundance of the genus Clostridium was significantly higher in the PB than in the RB, whereas the abundance of Candidatus_Hepatoplasma and Vibrio was significantly lower in the PB than in the RB. The prediction function of KEGG enrichment showed that the abundance of Amino acid metabolism, Biosynthesis of Other Secondary Metabolites, Transport and Catabolism, Cancers, and Nervous System, Substance Dependence were significantly higher in the PB, while the infectious diseases pathway was enriched in the RB. In summary, our results revealed significant differences in the composition and diversity of intestinal microbiota in the Cherax quadricarinatus between rice paddy and pond farming environments. The intestinal microbiota of the Cherax quadricarinatus grown in pond environments exhibit higher diversity and stability, manifested by an increase in beneficial bacteria abundance and a decrease in opportunistic pathogens. These findings significantly improve understanding of the complex relationship among Cherax quadricarinatus, intestinal microbiota, and the environment.

Exploring the relationship between land use change patterns and variation in environmental factors within urban agglomeration - Rui Xiao; Hanyu Yin; Ruoxin Liu; Zhonghao Zhang; Sukhbaatar Chinzorig; Kun Qin; Wenfang Tan; Yi Wan; Zhi Gao; Chen Xu; Lumeng Liu; Tao Jia (Sustainable Cities and Society, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Polydatin: a potential NAFLD therapeutic drug that regulates mitochondrial autophagy through SIRT3-FOXO3-BNIP3 and PINK1-PRKN mechanisms - a network pharmacology and experimental investigation - Jing He; Yi-cai Qian; Ying-chuan Yin; Jing-rui Kang; Tian-rong Pan (Chemico-Biological Interactions, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Speed optimization for maximizing the ship’s economic benefits considering the Carbon Intensity Indicator (CII) - Rui Hua; Jingbo Yin; Shaohan Wang; Yi Han; Xinbo Wang (Ocean Engineering, 2024)

Meteorological to Agricultural Drought Propagation Time Analysis and Driving Factors Recognition Considering Time-Variant Characteristics - Chengguo Wu; Yin Xu; Juliang Jin; Yuliang Zhou; Boyu Nie; Rui Li; Yi Cui; Fei Tong; Libing Zhang (Water Resources Management, 2024)

Fungus reduces tetracycline-resistant genes in manure treatment by predation of bacteria - Lei Liu; Qianxi Yin; Yu Hou; Rui Ma; Yi Li; Zhenyu Wang; Ganggang Yang; Yu Liu; Hailei Wang (Science of The Total Environment, 2024)

Recombinant Klotho alleviates vancomycin-induced acute kidney injury by upregulating anti-oxidative capacity via JAK2/STAT3/GPx3 axis - MengMeng Wang; Yue Zhou; GuoXiang Hao; Yue E. Wu; Rui Yin; Yi Zheng; Wei Zhao (Toxicology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Analyzing “economy-society-environment” sustainability from the perspective of urban spatial structure: A case study of the Yangtze River delta urban agglomeration - Hanyu Yin; Rui Xiao; Xufeng Fei; Zhonghao Zhang; Zhi Gao; Yi Wan; Wenfang Tan; Xucheng Jiang; Wei Cao; Yuxiang Guo (Sustainable Cities and Society, 2023)

Holocene climatic controls on flooding regime along the Ussuri River in Northeast Asia - Zhenqing Zhang; Lin Li; Rui Yin; Lu Zhang; Kai Yi; He Ji; Haijiao Yin; Lili Huo (Science of The Total Environment, 2023)

Sustainable network analysis and coordinated development simulation of urban agglomerations from multiple perspectives - Hanyu Yin; Zhonghao Zhang; Yi Wan; Zhi Gao; Yuxiang Guo; Rui Xiao (Journal of Cleaner Production, 2023)

Tectonic boundaries in the South China Sea from aeromagnetic signature - Yao Luo; Hang Yin; Qiang Liu; Jingmin Li; Shihua Liu; Wei Gao; Rui Li; Yi Yang (Journal of Oceanology and Limnology, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Dependences and risk spillover effects between Bitcoin, crude oil and other traditional financial markets during the COVID-19 outbreak - Rui Zha; Lean Yu; Yi Su; Hang Yin (Environmental Science and Pollution Research, 2023)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Factors Associated with Intergenerational Instability of ATXN3 CAG Repeat and Genetic Anticipation in Chinese Patients with Spinocerebellar Ataxia Type 3 - Yi-Chu Du; Yin Ma; Ya-Ru Shao; Shi-Rui Gan; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Detecting changes in sediment overburden using distributed temperature sensing: an experimental and numerical study - Yi Rui; Robert Hird; Mei Yin; Kenichi Soga (Marine Geophysical Research, 2019)

An Analytical Solution for the Run-Out of Submarine Debris Flows - Yi Rui; Mei Yin (Marine Geodesy, 2019)

Centrifuge study on the runout distance of submarine debris flows - Mei Yin; Yi Rui; Yanyi Xue (Marine Georesources & Geotechnology, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Centrifuge Study on the Submarine Mudflows - Yi Rui; Mei Yin (Marine Geodesy, 2019)

Laboratory study on submarine debris flow - Mei Yin; Yi Rui (Marine Georesources & Geotechnology, 2018)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Meiothermus roseus sp. nov., a thermophilic bacterium isolated from a geothermal area - Hong Ming; Yan-Yan Duan; Qian-Qian Guo; Yi-Rui Yin; En-Min Zhou; Lan Liu; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)